Influence The Application Of The Paragraph Building Method In Arabic Language Learning To Increase The Writing Skill At Madrasah Aliyah Darul Faizin Catak Gayam Mojowarno Jombang - Abidin, Hasan (Ats-Tsaqofi: Jurnal Pendidikan dan Manajemen Islam, 2021)
This journal explains about " The Effect of Application of Paragraph Building Method in Arabic Language Learning to Increase Writing Skills at Madrasah Aliyah Darul Faizin Catak Gayam – Mojowarno - Jombang ". The choice of the title is based on the assumption that the Paragraph Building method is a learning method that prioritizes students' ideas, thus requiring students to be more creative in developing their ideas and putting them into writing or sentences. Because learning with this method is different from existing lessons, by exposing students to interesting themes, it is hoped that it can support students Writing Skills. The author takes two problem formulations to be studied, namely, how to apply the Paragraph Building method for class X students of Madrasah Aliyah Darul Faizin Catak Gayam Mojowarno Jombang, and the second formulation is how the effect of applying the Paragraph Building method to class X students at Madarasah Aliyah Darul Faizin. Research methods in writing this scientific work are quantitative research using the "t" test formula to analyze the data, because this type of research is an experimental type of research. This study aims to determine the significance of differences in the achievement level of students ' Writing Skills before and after using the Paragraph Building method on 75 students consisting of 2 classes. While the sample used was random sampling technique, the research sample was 36 students who were divided into two classes, namely the control class and the trial class. And data collection is done by observation, interviews, questionnaires and tests. Then the results obtained are that the Paragraph Building method has an effect on the Writing Skills of class X Madrasah Aliyah Darul Faizin students, with the details of the trial class the average score is 6.63 (initial test) and 7.91 (posttest), while the control mean scores were 6.38 (initial test) and 6.94 (post test). Thus there is an effect because between the two there is a difference of 0.97